Effect of foundation surface roughness on ultimate bearing capacity of an eccentrically loaded foundation - Pham Ngoc Vinh; Pham Ngoc Quang; Hoang Thang (Tạp chí Khoa học và Công nghệ, 2023)
The study extensively investigated the ultimate bearing capacity (UBC) of an eccentrically loaded foundation under two scenarios (horizontal sandy soil and sandy soil slope), utilizing the Rigid Plastic Finite Element Method (RPFEM). To precisely simulate a diverse range of frictional conditions on the foundation surface roughness, a novel joint element is introduced, capable of accommodating both perfectly rough and perfectly smooth foundations. A novel constitutive equation is presented to model these joint elements, significantly influencing the failure mechanism of the shallow foundation. The study also examines the impact of the friction strength ϕ on the normalized vertical load V/Vult. The RPFEM results reveal that the friction strength ϕ substantially influences the V/Vult ratio for sandy soil slopes, while its effect is found to be negligible for horizontal sandy soil.